Comprehensive review on patulin and Alternaria toxins in fruit and derived products - Bacha, Syed Asim Shah; Li, Yinping; Nie, Jiyun; Xu, Guofeng; Han, Lingxi; Farooq, Saqib (Frontiers in Plant Science, 2023)
Mycotoxins are toxic secondary metabolites produced by certain fungi, which can contaminate various food commodities, including fruits and their derived products. Patulin and Alternaria toxins are among the most commonly encountered mycotoxins in fruit and their derived products. In this review, the sources, toxicity, and regulations related to these mycotoxins, as well as their detection and mitigation strategies are widely discussed. Patulin is a mycotoxin produced mainly by the fungal genera Penicillium, Aspergillus, and Byssochlamys. Alternaria toxins, produced by fungi in the Alternaria genus, are another common group of mycotoxins found in fruits and fruit products. The most prevalent Alternaria toxins are alternariol (AOH) and alternariol monomethyl ether (AME). These mycotoxins are of concern due to their potential negative effects on human health. Ingesting fruits contaminated with these mycotoxins can cause acute and chronic health problems. Detection of patulin and Alternaria toxins in fruit and their derived products can be challenging due to their low concentrations and the complexity of the food matrices. Common analytical methods, good agricultural practices, and contamination monitoring of these mycotoxins are important for safe consumption of fruits and derived products. And Future research will continue to explore new methods for detecting and managing these mycotoxins, with the ultimate goal of ensuring the safety and quality of fruits and derived product supply.